Boundary Controller and Observer Design for Korteweg-De Vries Type Equations - Arabacı, Eda; Özsarı, Türker (Izmir Institute of Technology, 2017)
This thesis studies the back-stepping boundary controllability of Korteweg-de Vries (KdV) type equations posed on a bounded interval. The results on the back-stepping controllability of the KdV equation obtained in Cerpa and Coron (2013) and Cerpa (2012) are reviewed and extended to the KdV-Burgers (KdVB) equation. The stability of the KdVB equation is boosted to any desired exponential rate for sufficiently small initial data with a boundary feedback controller acting on the Dirichlet boundary condition. Moreover, the case that there is no full access to the system is considered. For these kinds of systems, an observer is constructed assuming an appropriate boundary measurement is available. The ideas about designing output feedback control for the KdV equation presented in Marx and Cerpa (2016), and Hasan (2016) are reviewed and extended to the KdVB model.

Bu tez, sonlu bir aralıkta düşünülen Korteweg-de Vries (KdV) tipi denklemlerin geri adım yöntemi ile sınırdan kontrol edilebilirliği üzerine bir çalışmadır. (Cerpa and Coron (2013)) ve (Cerpa (2012))’da bahsedilen KdV denklemi için geri adımlama tekniğinin sonuçları incelenmiş ve Korteweg-de Vries-Burgers (KdVB) denklemine genellenmiştir. Kararlılık, sol Dirichlet sınır ko¸sulunda etkili olan sınır geri besleme kontrol girdisine sahip sistemler için başlangıç koşulunun yeterince küçük olduğu durumda sağlanmaktadır. Ayrıca dikkat edilmesi gereken nokta, üssel azalma hızının tercih edilen kadar büyük olmasıdır. Dahası, sisteme tam erişim olmayan durum düşünülmüştür. Bu tür sistemler için, uygun bir sınır ölçümü mevcutken bir gözlemci dizaynı oluşturulabilir. (Krstic (2009)), (Marx and Cerpa (2016)) ve (Hasan (2016))’da sunulan KdV denklemi için çıktı geri besleme kontrolünün tasarlanması ile ilgili fikirler üzerinde durulmuştur ve KdVB modeline aktarılmıştır. Buna ek olarak, kapalı döngü sistemlerinin üssel kararlılığı, gözlemci durumlarını da içeren Volterra dönüşümüne dayanan geri adım yöntemi kullanılarak kanıtlanmıştır.
Korteweg-de Vries Tipindeki Denklemler için Sınır Kontrolü ve Gözlemci Dizaynı
Thesis (Master)--Izmir Institute of Technology, Mathematics, Izmir, 2017
Includes bibliographical references (leaves: 49-85)
Text in English; Abstract: Turkish and English
Keywords: Korteweg-de Vries (KdV) equations; Boundary controller